The relationship between multimorbidity and cognitive function in older Chinese adults: based on propensity score matching - Yumeng Zhang; Yumeng Zhang; Xiaoli Yuan; Zhixia Jiang; Rujun Hu; Heting Liang; Qingyun Mao; Yan Xiong; Jiabi Zhang; Mi Liu (Frontiers Media S.A., 2024)
ObjectiveThe goal of this study was to further validate the effect of multimorbidity on cognitive performance in older adults after controlling for confounders using propensity score matching (PSM).MethodsA cross-sectional survey of older adult people aged 60 years or older selected by convenience sampling was conducted in seven medical institutions, three communities, and five nursing homes in Zunyi City, Guizhou Province. The data collected included general information, health-related information, and Mini-Mental State Examination (MMSE) scores. Variables were controlled for confounders by PSM to analyze differences in cognitive ability between multimorbidity and nonmultimorbidity older adults. Logistic regression and multivariate-adjusted restricted cubic spline (RCS) curves for matched samples were used to assess the relationship between multimorbidity and cognitive decline.ResultsA total of 14,175 respondents were enrolled, and the mean age of the participants included in this study was 71.26 ± 7.1 years, including 7,170 (50. 58%) of the participants were males, 7,005 (49.42%) were females, and 5,482 participants (38.67%) were screened for cognitive decline. After PSM, logistic regression analysis revealed that multimorbidity was a risk factor for cognitive decline (OR = 1.392, 95% CI = 1.271-1.525, p < 0.001). The RCS show that the risk of cognitive decline is always greater in older adults with multimorbidity than in older adults without multimorbidity at the same age. Age, sex, marital status, educational level, monthly income, drinking status, participation in social activities, and exercise were influential factors for cognitive decline in older adults (p < 0.05). The incidence of cognitive decline in older adults with multimorbidity was also greater than that in older adults with one chronic disease (p < 0.001).ConclusionThe risk of cognitive decline in older adults with multimorbidity is greater than that in older adults without multimorbidity; therefore, the government should strengthen the prevention and treatment of multimorbidity in older adults to further protect their cognitive abilities.